Shaping sustainable solutions in fashion through design-led strategies, approaches, and practices - Erminia D’Itria; Federica Vacca (Discover Sustainability)
Abstract Today, growing concerns about the Earth's finite resources and escalating climate challenges have sparked a reassessment of industrial processes. This has led to a call for a more responsible and transparent approach across various sectors. The global conversation prominently revolves around sustainable development to foster diversity within a comprehensive framework to effectively address UNESCO's four pillars of sustainability: Environment, economy, society, and culture. The fashion industry, a highly significant and influential sector, has proven to be invasive due to resource-intensive processes that impact both the environment and the economy. Additionally, the industry's rich cultural content plays a substantial role in shaping social and cultural shifts. In this context, this article focuses on design as a catalyst for reform within the fashion industry's supply and value chain, steering it towards sustainability. The focus is on exploring emerging responsible practices aligned with evolving priorities, aspirations, and lifestyles to foster a systemic approach to sustainability in fashion. The discussion highlights design-led perspectives that support a sustainable transition, underscoring the necessity for a transformative mindset among designers. This involves adopting innovative strategies to promote responsible approaches and practices for contributing to a more sustainable future.